Observed platelet ice distributions in Antarctic sea ice: An index for ocean‐ice shelf heat flux. Issue 13 (14th July 2015) - Langhorne, P. J.; Hughes, K. G.; Gough, A. J.; Smith, I. J.; Williams, M. J. M.; Robinson, N. J.; Stevens, C. L.; Rack, W.; Price, D.; Leonard, G. H.; Mahoney, A. R.; Haas, C.; et al.
Abstract Antarctic sea ice that has been affected by supercooled Ice Shelf Water (ISW) has a unique crystallographic structure and is called platelet ice. In this paper we synthesize platelet ice observations to construct a continent‐wide map of the winter presence of ISW at the ocean surface. The observations demonstrate that, in some regions of coastal Antarctica, supercooled ISW drives a negative oceanic heat flux of −30 Wm−2 that persists for several months during winter, significantly affecting sea ice thickness. In other regions, particularly where the thinning of ice shelves is believed to be greatest, platelet ice is not observed. Our new data set includes the longest ice‐ocean record for Antarctica, which dates back to 1902 near the McMurdo Ice Shelf. These historical data indicate that, over the past 100 years, any change in the volume of very cold surface outflow from this ice shelf is less than the uncertainties in the measurements.